Preferences of Javan Langurs (Trachypithecus auratus) for Food Trees as a Foraging Behavior Marker in the Coban Pelangi Area, Malang Regency - Fudianto, Achmad; Rohman, Fatchur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Javan lutung (Trachypitecus auratus) is known as one of the endemic primates of Java, Bali, and Lombok, whose existence is classified as vulnerable. Anthropogenic practices such as illegal wildlife trade, hunting, and habitat reduction stimulate changes in habitat use decisions, foraging strategies, and restrictions on daily activities. The objectives of the study include: (1) analyzing the vegetation that constitutes the Javan langur's diet, (2) identifying the Javan langur's preferences for food trees as indicators of foraging behavior, and (3) analyzing the daily feeding behavior of Javanese langurs in the Coban Pelangi area. The results of the research show that there are 15 plant species from 6 families with the highest INP found in Calliandra calothyrsus with a value of 87.22%, while there are 5 types of plants that serve as food sources, with Phyllantus reticulatus being the highest preference at 6,15 (w>1), Ficus sp. 3, Ficus kurzii, Calliandra calothyrsus, and Dendrocnide stimulans. The feeding behavior of the Javan langur as a daily activity is carried out by grabbing leaf stalks with their hands, stripping them, and then eating the young leaves for 2-5 minutes while sitting.